Education ANALISIS LINGKUNGAN PERTEMANAN TERHADAP MINAT BELAJAR ANAK DI UPTD SDN PEJAGAN 1 BERDASARKAN PERSPEKTIF EKSISTENSIALISME: Kajian Perspektif Eksistensialisme dalam Pendidikan - Aris Muyessaroh; Kamelia Yuniar; Yoga Saputra; Izzah Fijriyah; Ita Indriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of friendships on children's learning interests at the UPTD SDN Pejagan 1 based on an existentialist perspective. This study uses a qualitative approach with a case study method. The research subjects included class teachers and students, while data were obtained through in-depth interviews and observations of classroom learning activities. The results show that friendships have a significant role in the level of children's learning interests. Supportive peers who have a high enthusiasm for learning can foster children's intrinsic motivation to learn, while less positive friendships tend to decrease their attention and participation in learning activities. Based on an existentialist perspective, children's learning interests are formed through self-awareness and freedom in choosing a social environment that gives meaning to their existence. Therefore, teachers need to facilitate healthy and supportive friendship interactions, so that students can develop learning interests independently and authentically according to their respective existential potential.